ANALISIS FINANCIAL DISTRESS PADA PERUSAHAAN BUMN YANG TERDAFTAR DI BEI - Khansa Safira Nasution (2022)
This study aims to examine and determine the effect of profitability, liquidity, leverage and cash flow on financial difficulties in state-owned companies listed on the Indonesia Stock Exchange. This study uses a sample of state-owned companies listed on the IDX in the 2017-2020 period with a sampling technique in the form of probability sampling. The hypothesis testing in this study uses logistic regression analysis through the E-Views 12 program. The results of this study state that there is an influence on the profitability variable on financial difficulties in state-owned companies listed on the IDX for the period of 2017 - 2020 while variables such liquidity, leverage and cash flow do not affect the financial condition of a company to cause financial difficulties.